Smoking is Associated with Poorer Quality-Based Outcomes in Patients Hospitalized with Spinal Disease - Bisson, Erica F.; Bowers, Christian A.; Hohmann, Samuel F.; Schmidt, Meic H. (Frontiers in Surgery, 2015)
Study design: Retrospective cross-sectional database analysis Objective: The cost of spine surgery is growing exponentially, and cost-effectiveness is a critical consideration. Smoking has been shown to increase hospital costs in general surgery, but this impact has not been reported in spinal surgery patients. The objective of this work was to evaluate the effect of smoking on cost and complications in a large sample of patients admitted for treatment of spinal disease. Methods: In 2012, the authors identified all inpatient admissions to all University HealthSystem Consortium (UHC) hospitals from 2005 to 2011 for spinal disease based on the principal diagnosis ICD-9-CM codes from the prospectively collected UHC database. Patient outcomes—including length of stay; complication, readmission, and intensive care unit admission rates, and total cost—were compared for non-obese smokers and nonsmokers using a two-sample t-test. Results: There were 137,537 patients, including 136,511 (122,608 non-smokers and 13,903 smokers) in the 4 largest diagnostic groups. Smoking was associated with increased complications and worse outcomes in 3 of these 4 groups. All outcomes in the two largest groups—fracture and dorsopathy—were worse in the smoking patients. Conclusions: Smoking patients admitted for spinal disease in the sample had worse outcomes, increased complications, and higher costs than their non-smoking counterparts. In the current health-care climate focused on cost-effectiveness, smoking represents a potentially modifiable area for cost reduction.